Revealing the Effect: How Google Slides Helps Improve Vocational Students' Writing Skills - Kusumaningrum, Dyah Rini; Pratiwi, Dwiyani (Universitas Hamzanwadi, 2024)
Despite the widespread integration of Google Slides in educational settings, its direct effect on students' writing skills has received limited attention, primarily focusing on students' perceptions rather than measurable outcomes. This research aimed to quantify the impact of Google Slides on enhancing students' abilities to construct descriptive texts, employing qualitative and quantitative methods to provide a comprehensive analysis. Conducted over eight weeks at a Vocational High School in Banyumas, Central Java, the study involved 36 tenth-grade students. Utilizing a mixed-methods design, observations and pre-post test scores were collected to assess the effectiveness of Google Slides in the classroom. The quantitative analysis of pre-and posttest results showed a significant improvement in writing skills (t(35) = -16.095, p < 0.001), indicating that Google Slides positively affects students’ writing capabilities. Qualitative observations further highlighted the tool's broader benefits, including increased motivation, readiness to learn, and enhanced vocabulary among participants. The study thus confirms the significant positive impact of Google Slides on students' writing development and offers insights into its potential as a valuable educational resource.